Feasibility and Acceptability of Screening and Brief Interventions to Address Alcohol and Other Drug Use among Patients Presenting for Emergency Services in Cape Town, South Africa. - Myers-Franchi, Bronwyn; Stein, Dan J; Mtukushe, Bulelwa; Sorsdahl, Katherine (2012)
Despite evidence from high income countries, it is not known whether screening and brief interventions (SBI) for alcohol and other drug (AOD) use are feasible to implement in low and middle income countries. This paper describes the feasibility and acceptability of a peer-led SBI for AOD-using patients presenting with injuries at emergency services in Cape Town, South Africa. Data were extracted from program records on the number of eligible patients screened and the number of program refusals. A questionnaire examined preliminary responses to the intervention for 30 patients who had completed the program and 10 emergency personnel. Peer counselors were also interviewed to identify barriers to implementation. Of the 1458 patients screened, 21% (305) met inclusion criteria, of which 74% (225) were enrolled in the intervention. Of the 30 patients interviewed, most (83%) found the program useful. Emergency personnel were supportive of the program but felt that visibility and reach could improve. Peer counselors identified the need for better integration of the program into emergency services and for additional training and support. In conclusion, with limited additional resources, peer-led SBIs for AOD use are feasible to conduct in South African emergency services and are acceptable to patients and emergency personnel.